Case report: Radiotherapy plus pneumococcal conjugate vaccine stimulates abscopal immune response in a patient with ALK+ NSCLC - Huang, Yong-Sheng; Li, Zhuo; Xiao, Ze-Fen; Li, Dan; Liu, Wen-Yang (Frontiers in Immunology, 2022)
Most patients with Anaplastic lymphoma kinase positive (ALK+) non-small cell lung cancer (NSCLC) could benefit from the treatment with selected tyrosine kinase inhibitors (TKI) for a period of time, but almost inevitably progress due to drug resistance. It was reported that these patients were generally unresponsive to immune-based therapies. Here, we reported stereotactic body radiotherapy (SBRT) combined with pneumococcal conjugate vaccine (PCV) produced excellent therapeutic outcomes in a patient after multiple lines of TKI treatment. The patient's metastasis lesion experienced regression after SBRT for lumbar spine. Unexpectedly, the patient also experienced an abscopal complete pathological response (CPR) just after combination use of SBRT and PCV. Biopsy analysis indicated the primary lung lesion was map-like necrotic and infiltrated by tumor-infiltrating lymphocytes (TILs), and multifocal granulomas and early tertiary lymphoid structures (TLS) were formed. Our case reported that radiotherapy plus PCV could specifically stimulate immune response and remodel the tumor immune microenvironment in TKI-resistant NSCLC, which may provide a new perspective for future immunotherapy in this challenging clinical situation.